Photophysical properties of ligand localized excited state in ruthenium(ii) polypyridyl complexes: a combined effect of electron donor-acceptor ligand - Verma, Sandeep; Kar, Prasenjit; Das, Amitava; Ghosh, Hirendra Nath (Dalton Trans, 2011)
We have synthesized ruthenium(II) polypyridyl complexes (1) Ru(II)(bpy)2(L1), (2) Ru(II)(bpy)2(L2) and (3) Ru(II)(bpy)(L1)(L2), where bpy = 2,2′-bipyridyl, L1 = 4-[2-(4′-methyl-2,2′-bipyridinyl-4-yl)vinyl]benzene-1,2-diol) and L2 = 4-(N,N-dimethylamino-phenyl)-(2,2′-bipyridine) and investigated the intra-ligand charge transfer (ILCT) and ligand–ligand charge transfer (LLCT) states by optical absorption and emission studies. Our studies show that the presence of electron donating –NMe2 functionality in L2 and electron withdrawing catechol fragment in L1 ligands of complex 3 introduces low energy LLCT excited states to aboriginal MLCT states. The superimposed LLCT and MLCT state produces redshift and broadening in the optical absorption spectra of complex 3 in comparison to complexes 1 and 2. The emission quantum yield of complex 3 is observed to be extremely low in comparison to that of complex 1 and 2 at room temperature. This is attributed to quenching of the 3MLCT state by the low-emissive 3LLCT state. The emission due to ligand localized CT state (ILCT and LLCT) of complexes 2 and 3 is revealed at 77 K in the form of a new luminescence band which appeared in the 670–760 nm region. The LLCT excited state of complex 3 is populated either via direct photoexcitation in the LLCT absorption band (350–700 nm) or through internal conversion from the photoexcited 3MLCT (400–600 nm) states. The internal conversion rate is determined by quenching of the 3MLCT state in a time resolved emission study. The internal conversion to LLCT and ILCT excited states are observed to be as fast as ∼200 ps and ∼700 ps for complexes 3 and 2, respectively. The present study illustrates the photophysical property of the ligand localized excited state of newly synthesized heteroleptic ruthenium(II) polypyridyl complexes.